2013
DOI: 10.1136/jech-2012-202182
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ increased risk for disability pension: social confounding or health-mediated effects? Gender-specific analyses of the Hordaland Health Study cohort

Abstract: Socioeconomic status confounded the smoking-related risk for disability pension; for female heavy smokers, however, a significant increased risk persisted after adjustment. Women may be particularly vulnerable to heavy smoking and to its sociomedical consequences, such as disability pension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Some studies have shown smoking to be a significant risk factor for disability pension [37,38]. Haukness et al, however, found that especially among men, this association is mainly explained by the different socioeconomic status of smokers and non-smokers [39]. In our study, only a high serum cotinine level, proving current active smoking, associated with a slightly increased risk of disability pension (Table 3).…”
Section: Discussioncontrasting
confidence: 52%
“…Some studies have shown smoking to be a significant risk factor for disability pension [37,38]. Haukness et al, however, found that especially among men, this association is mainly explained by the different socioeconomic status of smokers and non-smokers [39]. In our study, only a high serum cotinine level, proving current active smoking, associated with a slightly increased risk of disability pension (Table 3).…”
Section: Discussioncontrasting
confidence: 52%
“… 13–15 The association between smoking and disability retirement appears to be dose-dependent, that is, the risk of disability retirement tends to increase with heavier smoking. 6–8 12 However, some studies have only examined current smoking, 9 16 and in a large study comprising 11 European countries, current smoking was unassociated with exit from the labour market due to disability. 17 Studies focused on smoking have sometimes considered physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an earlier study found that heavy smoking is associated with the risk of disability retirement among women even after adjusting for physical activity, while the association attenuated among men after adjusting for socioeconomic position and further by physical activity. 12 Both smoking and physical inactivity independently increase the risk of disability retirement, while physical activity could decrease the risk of disability retirement. Although some studies have had only self-reported data on work disability, 14 15 a recent meta-analysis further supported the importance of physical inactivity to the risk of disability retirement.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses were based on a 5-year observation period for medication adherence, including 2 years before and 2 years after the year of retirement. Data were stratified by gender because of gender differences in cardiovascular disease rates[ 1 ], in adherence to cardiovascular medication[ 6 , 19 ], in early and old-age retirement[ 20 22 ], and in the effects of illnesses and life transitions on adherence to some cardio-preventive medications. [ 11 , 23 ] Analyses were performed separately for those with at least one statin dispensation during a calendar year (continuers) and those with no dispensations (discontinuers).…”
Section: Methodsmentioning
confidence: 99%